Targeting AKT/mTOR and Bcl-2 for Autophagic and Apoptosis Cell Death in Lung Cancer: Novel Activity of a Polyphenol Compound - Sucharat Tungsukruthai; Onrapak Reamtong; Sittiruk Roytrakul; Suchada Sukrong; Chanida Vinayanwattikun; Pithi Chanvorachote (MDPI AG, 2021)
Autophagic cell death (ACD) is an alternative death mechanism in resistant malignant cancer cells. In this study, we demonstrated how polyphenol stilbene compound PE5 exhibits potent ACD-promoting activity in lung cancer cells that may offer an opportunity for novel cancer treatment. Cell death caused by PE5 was found to be concomitant with dramatic autophagy induction, as indicated by acidic vesicle staining, autophagosome, and the LC3 conversion. We further confirmed that the main death induction caused by PE5 was via ACD, since the co-treatment with an autophagy inhibitor could reverse PE5-mediated cell death. Furthermore, the defined mechanism of action and upstream regulatory signals were identified using proteomic analysis. Time-dependent proteomic analysis showed that PE5 affected 2142 and 1996 proteins after 12 and 24 h of treatment, respectively. The crosstalk network comprising 128 proteins that control apoptosis and 25 proteins involved in autophagy was identified. Protein-protein interaction analysis further indicated that the induction of ACD was via AKT/mTOR and Bcl-2 suppression. Western blot analysis confirmed that the active forms of AKT, mTOR, and Bcl-2 were decreased in PE5-treated cells. Taken together, we demonstrated the novel mechanism of PE5 in shifting autophagy toward cell death induction by targeting AKT/mTOR and Bcl-2 suppression.